DESIGN AND IMPLEMENTATION OF E-COMMERCE SYSTEM WITH TECHNOLOGY FRAMEWORK ORIENTED OBJECT - Dwi Surjono, Herman (Jurnal Penelitian Saintek, 2015)
The purpose of this' research was to design and to implement an e commerce (electronic commerce) system using components and object oriented frameworks technology. The research begins with analyzing and identifying specifications, which are categorized functionally into modules and objects. The objects are grouped into three logical categories: presentation aspects, business rules and data, and objects that accept and interpret user requests and control the business objects. The result is an e-commerce system running on local server of J2EE with URL http://localhost:8000/rbi/.Byaccessingthesystem,it is assumed that the performance would be in line with the expected research goals. The important web pages of the system among others are main page, product category, product item list, detail item description, shopping cart, log-in and log-out page, order notes, and other supporting pages. This e-commerce system was designed to be adapted to other products easily.